Role of IgG avidity in eyes with active Toxoplasma retinochoroiditis - Lakhmawar, Pratik; Kelgaonkar, Anup; Patel, Anamika; Khalsa, Ashish; Basu, Soumyava (Indian journal of ophthalmology, 2024)
Purpose: To study the role of Toxoplasma IgG avidity in evaluating the stage of systemic infection during manifestation as toxoplasma retinochoroiditis and its clinical implications in eastern India. Methods: Retrospective chart review of Toxoplasma retinochoroiditis cases with Toxoplasma serology for IgG, IgM, and IgG avidity. Results: Included in this study were 17 eyes of 17 patients who had active retinitis located in the macula (14), mid-periphery (2), or periphery (1). They were either primary lesions (12) or reactivations (5). All the cases had Toxoplasma IgG positive; one case had IgM positivity, while all the cases had high IgG avidity values. IgG avidity had a positive correlation with the duration of symptoms. Conclusion: We observed high IgG avidity values in active retinochoroiditis in both primary ocular Toxoplasmosis and reactivation subgroups. These results indicate a late ocular manifestation after initial systemic infection with a possible incubation period ranging from 5 weeks to 5 months.